Dampak Game Online “Free Fire” Bagi Siswa Kelas V Sekolah Dasar di Kota Pekanbaru - Muhammad Faisal Z.; Dea Mustika (Universitas Negeri Padang, 2023)
The importance of this research is because student motivation and learning outcomes have decreased and there are still many negative impacts caused by the online game Free Fire. The aim of this research is to describe the positive and negative impacts of the online game Free Fire on students at SDN 193 Pekanbaru. This research is descriptive research with a qualitative approach model. Primary data sources obtained by researchers through interviews, observation and documentation. Researchers interviewed teachers at SDN 193 Pekanbaru where the teachers learned about the problem of decreasing student motivation and learning outcomes due to addiction to online games. Data collection techniques include interviews, observation and documentation. The validity of the data was tested using technical triangulation and source triangulation. Data analysis uses the Miles & Huberman technique which includes stages of data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that the teacher has identified the symptoms of problems experienced by students due to the impact of the online game Free Fire, so that the teacher has provided a solution to these problems.